Effects of Increased Electric Vehicles into a Distribution Network. (January 2019) - Anastasiadis, Anestis G.; Kondylis, Georgios P.; Polyzakis, Apostolos; Vokas, Georgios
Abstract: Power grids face a new and important challenge: the oncoming mass penetration of plug-in Electrical Vehicles (EVs). Nevertheless, the architectures of transmission and distribution grids are still focused on traditional design and operational rules. Consequently, it is necessary to predict the adequate solutions for the problems which are going to rise to the electrical and production grids as well as the effect on their commercial operation as a result of the gradual integration of EVs into the network. For example major congestion problems may appear in already heavily loaded grids as well as voltage profile problems mainly in radial networks, particularly if the peak load periods coincide with EV charging periods. In this paper the impacts of penetration of EVs on selected buses of a Distribution Network are assessed. The analysis takes into account driving profiles of EV owners, type of vehicle (battery capacity, energy consumption), travelling distance, road conditions etc, and approximates the hourly allocation of the energy requirements under various EV charging strategies. A steady state analysis toolbox is used to their impact to its operation.